Malaysia’s Development Policies - Jauhar, Junaimah; Abdul Ghani, Ahmad Bashawir; Islam, Rabiul (Springer, 2016)
New Economic Model and all other Malaysia’s development policies and remedial measures demonstrate that in order to enhance development and provide a jump start to its economy, Malaysia obviously have to institute serious structural transformations.All these moves signify a substantial move towards this direction. What is more important and crucial at this juncture is converting those into real workable policies and the obligation to carry them out. It is envisioned that once all these measures are put in place and have been implemented adequately and fittingly, Malaysia will be the best place for all and it is anticipated that this will be able to keep in check Malaysia’s brain drain issue.